VALIDATION OF A NEW WATER-PERFUSED HIGH-RESOLUTION MANOMETRY SYSTEM - MARIOTTO, Rogério (Arq Bras Cir Dig, 2021)
BACKGROUND: High-resolution manometry is more costly but clinically superior to conventional manometry. Water-perfused systems may decrease costs, but it is unclear if they are as reliable as solid-state systems, and reference values are interchangeable. AIM: To validate normal values for a new water-perfusion high-resolution manometry system. METHODS: Normative values for a 24-sensors water perfused high-resolution manometry system were validated by studying 225 individuals who underwent high resolution manometry for clinical complaints. Patients were divided in four groups: group 1 - gastroesophageal reflux disease; group 2 - achalasia; group 3 - systemic diseases with possible esophageal manifestation; and group 4 - dysphagia. RESULTS: In group 1, a hypotonic lower esophageal sphincter was found in 49% of individuals with positive 24 h pH monitoring, and in 28% in pH-negative individuals. In groups 2 and 3, aperistalsis was found in all individuals. In group 4, only one patient (14%) had normal high-resolution manometry. CONCLUSIONS: The normal values determined for this low-cost water-perfused HRM system with unique peristaltic pump and helicoidal sensor distribution are discriminatory of most abnormalities of esophageal motility seen in clinical practice.